2020
DOI: 10.1021/acsami.0c09592
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an Ultrahigh Power Factor and Enhanced Thermoelectric Performance in TiS2 via Microstructural Texture Engineering

Abstract: Layered 1T-type TiS2 powders were pretreated by an ethanol-based shear pulverization process, which showed outstanding effectiveness in reducing the average grain size and narrowing the size distribution while maintaining high crystallinity and plate-shaped morphology. The resulting bulk ceramics densified by spark plasma sintering possessed a highly (00l)-oriented texture and pronounced anisotropy. They showed a noticeably increased σ and an unaffected S in the in-plane direction due to the increased carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Seebeck coefficient at 233 K was recorded as −55 µV/K. This value increased to approximately −72 µV/K by heating the film to 323 K. The obtained values are all negative, indicating that this semiconductor has n-type carriers, which is similar to that of TiS 2 reported by many workers [ 35 , 36 , 37 , 38 ]. The calculated power factor, PF, is shown in Figure 5 b.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Seebeck coefficient at 233 K was recorded as −55 µV/K. This value increased to approximately −72 µV/K by heating the film to 323 K. The obtained values are all negative, indicating that this semiconductor has n-type carriers, which is similar to that of TiS 2 reported by many workers [ 35 , 36 , 37 , 38 ]. The calculated power factor, PF, is shown in Figure 5 b.…”
Section: Resultssupporting
confidence: 79%
“…Moreover, due to its elegant features such as an attractive structure, lightweight material, cheap chalcogenide, and high electrical conductivity with a semi-metallic behavior [ 31 ], TiS 2 has been employed as a cathode material in rechargeable batteries [ 32 ], electrode materials of pseudocapacitors [ 33 ], and as a sensor material for uric acid determination [ 34 ]. In addition to these applications, the single crystals of TiS 2 were reported to show good TE performance [ 35 , 36 , 37 , 38 ]. It was also involved in nanocomposites [ 39 ] for producing flexible TE materials and devices [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…FWHM of B1 is 0.233° while it is 1.25° in the previous study). Finally, very recently, Gu et al [ 36 ] observed a significant increase of the thermoelectric power factor on a mechanically exfoliated and restacked at high-temperature bulk pristine TiS 2 . In this independent study Gu et al also demonstrate that the crystal quality seems to be the key parameter in achieving the high thermoelectric properties in 2D based materials.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 As α, σ, and κ e strongly couple with each other, it is not easy to boost ZT values simply by adjusting any one of these parameters. 4 In order to optimize the electrical properties, a series of carrier engineering strategies, including the band convergence engineering, 5,6 band alignment engineering, 7,8 resonant level effect, 9 spin− orbit effect, 10,11 magnetoelectric effect, 12−14 modulation doping effect, 15,16 texture engineering, 17,18 and so forth, have emerged to improve the power factor. Meanwhile, various phonon engineering approaches have also been employed to lower the lattice thermal conductivity via phonon−liquid effect, 19,20 lattice softening effect, 21,22 hierarchical architecture engineering, 23−25 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The TE performance of a material is gauged by its dimensionless figure-of-merit ZT value, defined as ZT = α 2 σ T /(κ L + κ e ), where α, σ, κ L , κ e , and T are the Seebeck coefficient, electrical conductivity, lattice thermal conductivity, electronic thermal conductivity, and the absolute temperature, respectively. , As α, σ, and κ e strongly couple with each other, it is not easy to boost ZT values simply by adjusting any one of these parameters . In order to optimize the electrical properties, a series of carrier engineering strategies, including the band convergence engineering, , band alignment engineering, , resonant level effect, spin–orbit effect, , magnetoelectric effect, modulation doping effect, , texture engineering, , and so forth, have emerged to improve the power factor. Meanwhile, various phonon engineering approaches have also been employed to lower the lattice thermal conductivity via phonon–liquid effect, , lattice softening effect, , hierarchical architecture engineering, and so forth.…”
Section: Introductionmentioning
confidence: 99%